2018
DOI: 10.3892/ol.2018.9185
|View full text |Cite
|
Sign up to set email alerts
|

Study on the expression of p53 and MMP‑2 in patients with lung cancer after interventional therapy

Abstract: The aim of the study was to investigate the expression of tumor suppressor gene p53 and MMP-9 in non-small cell lung cancer (NSCLC) before and after chemotherapy, and investigate its association with the effect of chemotherapy and prognosis. Fifty-eight elderly NSCLC patients comprised the observation group. Reverse transcription-quantitative polymerase chain reaction (RT-qPCR) was used to detect the expression of p53 and MMP-9 in lung cancer tissues before and after chemotherapy. Immunohistochemistry and west… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
2
0
0
Order By: Relevance
“…An example is cisplatin, which is widely used in NSCLC as an adjuvant therapy. Studies on tumor tissue fragments taken from patients before the initiation of treatment with cisplatin and vinorelbine and two weeks after the end of the treatment cycle showed a statistically significant decrease in MMP2 gene expression compared to the baseline [31]. Similar results were also obtained by Liang H et al who studied the effect of the use of cisplatin on the level of expression of MMP-2 and MMP-9 proteins in a human lung cancer cell line.…”
Section: Discussionsupporting
confidence: 77%
“…An example is cisplatin, which is widely used in NSCLC as an adjuvant therapy. Studies on tumor tissue fragments taken from patients before the initiation of treatment with cisplatin and vinorelbine and two weeks after the end of the treatment cycle showed a statistically significant decrease in MMP2 gene expression compared to the baseline [31]. Similar results were also obtained by Liang H et al who studied the effect of the use of cisplatin on the level of expression of MMP-2 and MMP-9 proteins in a human lung cancer cell line.…”
Section: Discussionsupporting
confidence: 77%
“…Furthermore, miR-338-3p overexpression and the knockdown of MMP-2 could suppress the human neuroblastoma cell proliferation, invasion, and EMT pathway but promote the cell apoptosis. Moreover, the data of upregulated MMP-2 expression also agreed with those reported in glioblastomas and lung cancer [25,26]. Additionally, we observed that MMP-2 was directly targeted by miR-338-3p.…”
Section: Discussionsupporting
confidence: 89%